KONSEP MANAJEMEN SUMBER DAYA MANUSIA : IMPLEMENTASI PADA INDUSTRI PERBANKAN SYARIAH - ROZALINDA ROZALINDA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The banking sector has a strategic role to support national development that lead to an increase in the distribution of development and its results. Various problems still constrain the development of Islamic financial institutions in Indonesia, including regulatory issues, management, and SDI. Of the overall Islamic banking existing SDI, SDI 90% of its currently do not have the educational background of sharia economy. Educational background sharia only 10% SDI islamic background. The purpose of this study was conducted to elucidate the pattern of recruitment of employees in Islamic banks. Then, uncovering the factors that causes a lack of SDI berlatang behind sharia recruited into a sharia bank employees. Then, formulate strategic steps College of Islamic Religion to improve the competence of its graduates to be ready to compete in the world of work. Employee recruitment process in Islamic banks through several stages namely, administrative Selection, Test first round of interviews, a written test, Physicotest, the second stage interview, Test health.